Understanding patient preference for physician attire in ambulatory clinics: a cross-sectional observational study. Issue 5 (9th May 2019) - Zollinger, Marc; Houchens, Nathan; Chopra, Vineet; Clack, Lauren; Schreiber, Peter Werner; Kuhn, Latoya; Snyder, Ashley; Saint, Sanjay; Petrilli, Christopher M; Sax, Hugo
Abstract : Objectives: We explored patient perceptions regarding physician attire in different clinical contexts and resultant effects on the physician–patient relationship. Setting: The 900-bed University Hospital Zurich, Switzerland. Participants: A convenience sample of patients receiving care in dermatology, infectious diseases and neurology ambulatory clinics of the University Hospital Zurich participated in a paper-based survey. Primary and secondary outcome measures: The survey instrument was randomised and showed photographs of male or female physicians wearing various forms of attire. On the basis of the respondents' ratings of how the physician's attire affected perceptions across five domains (knowledgeable, trustworthy, caring, approachable and comfort with the physician), a composite preference score for attire was calculated as the primary outcome. Secondary outcomes included variation in preferences by respondent characteristics and context in which care was provided. Results: Of 834 patient respondents (140 in dermatology, 422 in infectious diseases and 272 in neurology), 298 (36%) agreed that physician attire was important. When compared with all available choices, the combination of white scrubs with white coat was rated highest while a business suit ranked lowest. Variation in preferences and opinions for attire were noted relative to respondent demographics and the clinical setting in which the survey was administered. For example, compared with younger patients, respondents ≥65 years of age more often reported that physician dress was both important to them and influenced how happy they were with their care (p=0.047 and p=0.001, respectively). Conclusions: Outpatients at a large Swiss University hospital prefer their physicians to be dressed in white scrubs with white coat. Substantial variation among respondents based on demographics, type of physician and clinical setting were observed. Healthcare systems should consider context of care when defining policies related to dress code.